2018
DOI: 10.1016/j.mayocp.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 and TLR4 Expression in Epithelial Ovarian Cancer

Abstract: ObjectiveTo evaluate myeloid differentiation primary response gene 88 (MyD88) and Toll-like receptor 4 (TLR4) expression in relation to clinical features of epithelial ovarian cancer, histologic subtypes, and overall survival.Patients and MethodsWe conducted centralized immunohistochemical staining, semi-quantitative scoring, and survival analysis in 5263 patients participating in the Ovarian Tumor Tissue Analysis consortium. Patients were diagnosed between January 1, 1978, and December 31, 2014, including 286… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…MYD88, a toll-like receptor signaling adaptor protein, is critical in the development of pancreatic cancer, epithelial ovarian cancer, and bladder cancer. [40][41][42] Finally, the roles of these tRFs in the development of BC were further confirmed by analyzing their target genes, and they were considered to serve as potential biomarkers for the detection of EBC.…”
Section: Discussionmentioning
confidence: 94%
“…MYD88, a toll-like receptor signaling adaptor protein, is critical in the development of pancreatic cancer, epithelial ovarian cancer, and bladder cancer. [40][41][42] Finally, the roles of these tRFs in the development of BC were further confirmed by analyzing their target genes, and they were considered to serve as potential biomarkers for the detection of EBC.…”
Section: Discussionmentioning
confidence: 94%
“…To investigate the underlying mechanism of miR-362-3p in OC, we tested the potential target gene of miR-362-3p, MyD88. A previous study showed strong MyD88 staining and poor survival in low-grade serous ovarian cancer [ 26 ]. The online software Targetscan showed that MyD88 is a potential targeted gene.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it showed that in high-grade serous ovarian carcinomas (HGSOCs). Interesting, the function of MyD88 seemed have related with the grade of serous ovarian cancer [ 26 ]. It showed that strong MyD88 expression was modestly associated with shortened overall survival, and in low-grade serous ovarian cancer (LGSOC), strong expression of both MyD88 and TLR4 was associated with favorable survival.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 was the first member of the TLR family to be discovered, by Medzhitov et al in 1997 (14). It was verified that TLR4 is expressed in many types of tumors, such as hepatocellular carcinoma, glioblastoma, lung, breast, ovarian and colon cancers as well as melanoma (15)(16)(17)(18)(19)(20)(21). OSCC was also among the tumors that highly express this receptor (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 94%